Batin Dance from Ritual to Performing Arts in Liwa Community West Lampung Regency Lampung Province - Nur Sintia; Erlinda Erlinda; Surherni Surherni (Universitas Negeri Semarang, 2023)
Batin dance is an expression of the people's joy in welcoming the sultan's arrival. Batin dance has developed from a ritual function to a performance function. This research aims to determine the development of the function of the batin dance from ritual to performing arts. This research used a descriptive analysis method, and it was guided by facts found during the field research. A historical approach was used to determine the development of a ritual function to a performance function. The research results show that the batin dance has developed from a ritual function to a performance function starting from the props, music, performance venue, and performance time. It can be seen through the batin dance performance at the GSMS event. The development of the batin dance is present in society, but Saibatin still maintains the batin dance in the kingdom as a prominent guest without reducing its sacred value.